Prague and Bohemia
1 online resource
Keywords: This book explores the remarkable flourishing of art and architecture in Bohemia, and Prague as it became the political centre of Charles IV's Holy Roman Empire. It focuses on cultural exchange and the links that can be traced through the artwork across Europe.